438 RECURRENT MENINGEAL SYMPTOMS IN PATIENTS TREATED FOR CRYPTOCOCCUS NEOFORMANS MENINGITIS AND ON HIGHLY ACTIVE AANTIRETROVIRAL THERAPY. (1st January 2005) - Solomon, C.; Masliah, A.; Mathews, C.; McCutchan, A.
Abstract : Background: Patients treated successfully for Cryptoccus neoformans meningitis (CnM) and initiating highly active antiretroviral therapy (HAART) may have recurrent CNS symptoms for a number of reasons including relapsing CnM or immune reconstitution inflammatory syndrome (IRIS). Anecdotal reports of CnM-related IRIS have been published, but data on its incidence and differential diagnosis have not. Methods: From 1994-2004, 12 (24%) of 52 AIDS patients with treated CnM presented to UCSD with recurrent CNS symptoms following initiation of HAART. Their charts were systematically reviewed, relevant features abstracted, and ultimate diagnoses deduced from symptoms, CD4 counts, duration of HAART, and CSF pleocytosis, cultures, and cryptococcal antigen (Crag) titers. Results: These 12 patients were ultimately categorized in 5 groups: 1) meningeal IRIS (pleocytosis without viable Cn, n=4 or 33%), 2) focal IRIS (cerebral cryptococcoma or localized IRIS at site of treated cryptococcoma as suggested by focal encephalitis on CT or MRI scans of the brain, n=2 or 17%), 3) recurrent CnM during HAART therapy (CnM by culture while on HAART, n=2 or 17%), 4) probable CnM during initiation of HAART (rising Crag titers but negative cultures after starting HAART, n=1 or 8%) and 5) a syndrome simulating CnM following initiation of HAART, but undiagnosed by extensive evaluations and self-limited, n= 25%). Patients with meningeal IRIS (group 1) presented a median of 28 days after HAART initiation with symptoms of CnM that resulted in hospitalization and lasted about 2 weeks. Common findings in CnM-related meningeal IRIS were leptomeningeal enhancement on MRI, increased pleocytosis compared to their initial episodes of CnM, and elevated ICP (≥25 cm H2O) leading to death in one case. Conclusions: Recurrent symptoms in patients with prior CnM while on HAART occurred in 24% of 52 patients at risk and appear to be caused more frequently by meningeal (33%) or focal (17%) IRIS (total 50%) than by relapsing CnM (17 - 25%). Expanding use of HAART in developing countries where CnM is common will increase experience with CnM-related IRIS for which management has not been developed or tested.